Theoretical Concepts of X-Ray Nanoscale Analysis Theory and Applications - Benediktovich, Andrei; Feranchuk, Ilya.; Ulyanenkov, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book provides a concise survey of modern theoretical concepts of X-ray materials analysis. The principle features of the book are: basics of X-ray scattering, interaction between X-rays and matter and new theoretical concepts of X-ray scattering. The various X-ray techniques are considered in detail: high-resolution X-ray diffraction, X-ray reflectivity, grazing-incidence small-angle X-ray scattering and X-ray residual stress analysis. All the theoretical methods presented use the unified physical approach. This makes the book especially useful for readers learning and performing data analysis with different techniques. The theory is applicable to studies of bulk materials of all kinds, including single crystals and polycrystals as well as to surface studies under grazing incidence. The book appeals to researchers and graduate students alike.
Basic principles of the interaction between X-rays and matter -- X-ray reflectivity -- High-resolution X-ray diffraction -- Grazing-incidence small-angle X-ray scattering -- Theory of X-ray scattering from imperfect crystals -- X-ray diffraction for evaluation of residual stresses in polycrystals -- Methods of mathematical and physical optimization of X-ray data analysis.
Keywords: Physics; Surfaces (Physics).; Physics; Measurement Science and Instrumentation; Characterization and Evaluation of Materials; Theoretical, Mathematical and Computational Physics; Applied and Technical Physics; Spectroscopy and Microscopy